IDNLearn.com offers a collaborative platform for sharing and gaining knowledge. Ask your questions and receive detailed and reliable answers from our experienced and knowledgeable community members.
Sagot :
Let's carefully analyze each step of Jerome's solution to identify where an error might have occurred.
Step 1: Subtraction Property of Equality
Jerome started with the equation:
[tex]\[ \frac{1}{3} x + \frac{5}{6} = 1 \][/tex]
He then subtracted [tex]\(\frac{5}{6}\)[/tex] from both sides:
[tex]\[ \frac{1}{3} x + \frac{5}{6} - \frac{5}{6} = 1 - \frac{5}{6} \][/tex]
This simplifies to:
[tex]\[ \frac{1}{3} x = 1 - \frac{5}{6} \][/tex]
Calculating the right side:
[tex]\[ 1 - \frac{5}{6} = \frac{6}{6} - \frac{5}{6} = \frac{1}{6} \][/tex]
So far, there's no error, and we have:
[tex]\[ \frac{1}{3} x = \frac{1}{6} \][/tex]
Step 2: Evaluating the Expression
Jerome mentioned correcting this step to:
[tex]\[ \frac{1}{3} x = \frac{1}{6} - \frac{5}{6} \][/tex]
It appears he tried calculating [tex]\(\frac{1}{6} - \frac{5}{6}\)[/tex]:
[tex]\[ \frac{1}{6} - \frac{5}{6} = \frac{1 - 5}{6} = \frac{-4}{6} = \frac{-2}{3} \][/tex]
At this point, the equation should be:
[tex]\[ \frac{1}{3} x = \frac{-2}{3} \][/tex]
Step 3: Multiply by the Reciprocal
Then, to isolate [tex]\(x\)[/tex], multiply both sides by the reciprocal of [tex]\(\frac{1}{3}\)[/tex], which is [tex]\(3\)[/tex]:
[tex]\[ x = \frac{-2}{3} \times 3 \][/tex]
Simplifying:
[tex]\[ x = -2 \][/tex]
Step 4: The Final Answer
So, the correct value of [tex]\(x\)[/tex] is:
[tex]\[ x = -2 \][/tex]
Conclusion:
Jerome made an error in step 1 when simplifying [tex]\(\frac{1}{3} x = 1 - \frac{5}{6}\)[/tex] by stating that it equals [tex]\(\frac{1}{6}\)[/tex] instead of evaluating it directly. Correctly evaluated, [tex]\(1 - \frac{5}{6} = \frac{1}{6}\)[/tex].
Therefore:
- Jerome made no error in steps 2, 3, and 4.
- The correct calculation would yield [tex]\(x = -2\)[/tex], and any errors in steps 2, 3, and 4 would have caused incorrect results if they were significant.
Thus, despite the arduous presentation and potential confusions, the errors and corrections align - Jerome should ensure correctly simplifying fractional expressions meticulously in all steps consistently.
Step 1: Subtraction Property of Equality
Jerome started with the equation:
[tex]\[ \frac{1}{3} x + \frac{5}{6} = 1 \][/tex]
He then subtracted [tex]\(\frac{5}{6}\)[/tex] from both sides:
[tex]\[ \frac{1}{3} x + \frac{5}{6} - \frac{5}{6} = 1 - \frac{5}{6} \][/tex]
This simplifies to:
[tex]\[ \frac{1}{3} x = 1 - \frac{5}{6} \][/tex]
Calculating the right side:
[tex]\[ 1 - \frac{5}{6} = \frac{6}{6} - \frac{5}{6} = \frac{1}{6} \][/tex]
So far, there's no error, and we have:
[tex]\[ \frac{1}{3} x = \frac{1}{6} \][/tex]
Step 2: Evaluating the Expression
Jerome mentioned correcting this step to:
[tex]\[ \frac{1}{3} x = \frac{1}{6} - \frac{5}{6} \][/tex]
It appears he tried calculating [tex]\(\frac{1}{6} - \frac{5}{6}\)[/tex]:
[tex]\[ \frac{1}{6} - \frac{5}{6} = \frac{1 - 5}{6} = \frac{-4}{6} = \frac{-2}{3} \][/tex]
At this point, the equation should be:
[tex]\[ \frac{1}{3} x = \frac{-2}{3} \][/tex]
Step 3: Multiply by the Reciprocal
Then, to isolate [tex]\(x\)[/tex], multiply both sides by the reciprocal of [tex]\(\frac{1}{3}\)[/tex], which is [tex]\(3\)[/tex]:
[tex]\[ x = \frac{-2}{3} \times 3 \][/tex]
Simplifying:
[tex]\[ x = -2 \][/tex]
Step 4: The Final Answer
So, the correct value of [tex]\(x\)[/tex] is:
[tex]\[ x = -2 \][/tex]
Conclusion:
Jerome made an error in step 1 when simplifying [tex]\(\frac{1}{3} x = 1 - \frac{5}{6}\)[/tex] by stating that it equals [tex]\(\frac{1}{6}\)[/tex] instead of evaluating it directly. Correctly evaluated, [tex]\(1 - \frac{5}{6} = \frac{1}{6}\)[/tex].
Therefore:
- Jerome made no error in steps 2, 3, and 4.
- The correct calculation would yield [tex]\(x = -2\)[/tex], and any errors in steps 2, 3, and 4 would have caused incorrect results if they were significant.
Thus, despite the arduous presentation and potential confusions, the errors and corrections align - Jerome should ensure correctly simplifying fractional expressions meticulously in all steps consistently.
We are delighted to have you as part of our community. Keep asking, answering, and sharing your insights. Together, we can create a valuable knowledge resource. For trustworthy and accurate answers, visit IDNLearn.com. Thanks for stopping by, and see you next time for more solutions.